Evolution Characteristics of Soil and Water Conservation Carbon Pool and Its Carbon Sink Potential in Typical Small Watershed of the Loess Plateau - HE Guokai; WANG Kaibo; REN Zongping; XU Guoce; DONG Pengbei; WANG Pu (Shuitu Baochi Xuebao)
[Objective] To investigate the evolution of soil carbon pool under catchment scale integrated soil and water conservation measures and evaluate the potential of soil and water conservation carbon sink. [Methods] Typical small watershed for soil and water loss control in the Loess Plateau was taken as the research object. Based on the analysis of the spatio-temporal changes of soil and water conservation measures in the watershed, the evolution law of soil organic carbon (SOC) pool under different soil and water conservation measures was clarified, and the potential of soil carbon sink under different soil and water conservation arrangements was evaluated with scenario analysis. [Results] (1) Compared with 1977, the total area of soil and water conservation measures in the basin increased by 32.9%, with the area of dam land, slope woodland, terraced grassland and terraced woodland increasing by 0.5%, 5.0%, 11.1% and 16.3%, respectively. The types of soil and water conservation measures were mainly terraced grassland and slope grassland. (2) The SOC density of different soil and water conservation measures increased compared with the bare land on the slope, and the SOC density of terraced measures was higher than that of slope measures. Terraced grassland, terraced woodland, slope grassland, channel grassland, slope woodland and dam land increased by 318.1%, 255.3%, 150.0%, 130.9%, 103.9% and 73.9%, respectively. (3) Soil and water conservation carbon storage in the study area increased from 264.5 t in 1977 to 332.8 t in 2022, with an increase of 25.8%, of which only 3.5% increased from 1977 to 2004, 22.4% increased from 2004 to 2015, and it then tended to be stable after 2015. (4) Under the condition that the soil below the ridge crest line remained unchanged, the soil organic carbon sequestration potential was the highest when the terraced grassland measures were adopted above the ridge crest line, with an increase of 20.5% compared with 2022. [Conclusion] The results indicate that, even in small watersheds with well-established soil and water conservation measures, optimizing the configuration of soil and water conservation measures can further enhance carbon sequestration potential.